Efektivitas Pemanfaatan Dana Klaim Asuransi Usahatani Padi (AUTP) di Subak Sengempel, Desa Bongkasa, Kecamatan Abiansemal Kabupaten Badung - SATWIKANI, ANAK AGUNG ARISTA; AMBARAWATI, I GUSTI AYU AGUNG; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018DO - 10.24843/JAA.2018.v07.i03.p02, 2018)
Effectiveness Of Utilization Of The Rice Crop Insurance (AUTP) Claims Fund at Subak Sengempel, Bongkasa Village, Abiansemal District Badung Regency AUTP was launched by the government as an effort to protect farmers from crop failure by providing claims that can be used as capital for the next season. This research aims to determine the response of farmers and the effectiveness of AUTP claims fund utilization. The research was done purposively in Subak Sengempel, Bongkasa Village, Abiansemal Sub-district of Badung Regency. Samples were 62 farmers who received claims fund. Data were collected through interviews, observation and documentation. Data analysis is descriptive qualitative and quantitative. The results shows that farmers respond positively to the AUTP program in terms of knowledge and attitude. The average knowledge of farmers reached 80% of the total expected knowledge about AUTP and the farmer's attitude were agreed with the average score is 4.10. Furthermore, by type of fund usage is effective category which is 90.32% of farmers use as a capital for rice cultivation for the next planting season. The utilization of AUTP claims funds viewed from the claims capability is effective to cover 110.31% cost of farming production per 0.25 ha up to planting and maintenance stages. In this research can be suggested the AUTP program needs to be continued and coordination between the parties involved should be maintained.